The Development and Psychometric Validation of an Arabic-Language Version of the Pain Catastrophizing Scale - Huda Abu-Saad Huijer; Souha Fares; Douglas J. French (Pain Research and Management)
Context. The Pain Catastrophizing Scale (PCS) is the most widely used measure of pain-specific catastrophizing. Objectives. The purpose of the present study was to develop and psychometrically evaluate an Arabic-language version of the PCS. Methods. In Study 1, 150 adult chronic nonmalignant pain patients seeking treatment at a hospital setting completed the PCS-A and a number of self-report measures assessing clinical parameters of pain, symptoms of depression, and quality of life. Study 2 employed a cold pressor pain task to examine the PCS-A in a sample of 44 healthy university students. Results. Exploratory factor analyses suggested a two-factor structure. Confirmatory factor analysis comparing the 2-factor model, Sullivan’s original 3-factor model, and a 1-factor model based on the total score all provided adequate fit to the data. Cronbach’s alpha coefficients across all models met or exceeded accepted standards of reliability. Catastrophizing was associated with higher levels of depression and increased pain intensity and interference. Catastrophizing predicted decreased quality of life, even after controlling for the contribution of gender, employment, depression, and pain interference. PCS-A scores were positively correlated with heightened experimental pain severity and decreased pain tolerance. Conclusion. The present results provide strong support for the psychometric properties of the PCS-A.